Model uncertainty and the effect of shall-issue right-to-carry laws on crime - Steven N. Durlauf; Salvador Navarro; David A. Rivers (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2014)
In this paper, we explore the role of model uncertainty in explaining the different findings in the literature regarding the effect of shall-issue right-to-carry concealed weapons laws on crime. In particular, we systematically examine how different modeling assumptions affect the results. We find little support for some widely used assumptions in the literature (e.g., population weights), but find that allowing for the effect of the law to be heterogeneous across both counties and over time is important for explaining the observed patterns of crime. In terms of model uncertainty, we find that there is substantial variation in the estimated effects for each model across all dimensions of the model space. This suggests that one should be cautious in using the results from any particular model to inform policy decisions.
Keywords: 330